1995
DOI: 10.3354/meps126299
|View full text |Cite
|
Sign up to set email alerts
|

Use of seabirds to monitor sea-surface temperatures and to validate satellite remote-sensing measurements in the Southern Ocean

Abstract: Changes in sea-surface temperature (SST) including the position of the sub-tropical convergence of the southern Indian Ocean were ascertained by using wandering albatrosses Dio~nedea exulans fitted with temperature recorders and by satellite tracking systcms. Fllght phases interspaced with frequent pauses on the sca means that albatrosses make useful tools for studying SST In the Southern Ocean, because in situ measurements (to validate satellite data) are rare because of the remoteness of the area. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Data were plotted using Elsa99 software (release 1.0, Soft & Technique Informatique). Locations were filtered such that those that suggested transit speeds > 3 m s -1 were excluded (Weimerskirch et al 1995, Bost et al 1997, Bonadonna et al 2000. The maximal distance from the colony reached by each seal was measured between the farthest point and the colony, and the total length of a foraging trip was obtained by summing all distances between 2 consecutive points of this trip.…”
Section: Methodsmentioning
confidence: 99%
“…Data were plotted using Elsa99 software (release 1.0, Soft & Technique Informatique). Locations were filtered such that those that suggested transit speeds > 3 m s -1 were excluded (Weimerskirch et al 1995, Bost et al 1997, Bonadonna et al 2000. The maximal distance from the colony reached by each seal was measured between the farthest point and the colony, and the total length of a foraging trip was obtained by summing all distances between 2 consecutive points of this trip.…”
Section: Methodsmentioning
confidence: 99%
“…winter season) and in locations (e.g. Southern Ocean) that are otherwise difficult to sample synoptically by more conventional means (Ancel et al 1992, Weimerskirch et al 1995. Current telemetry techniques deployed on foraging seabirds can provide information on prey distribution; e.g.…”
Section: Need For Seabirds As Indicatorsmentioning
confidence: 99%
“…An estimated 1000000 pairs of king penguins breed on the Crozet Archipelago, south-west Indian Ocean (Guinet et al 1995), and their annual food consumption is about 0.8 X 106 t, of which 85 to 90% is myctophid fish (Guinet et al 1996). The pelagic distribution of king penguins was first investigated at Crozet Archipelago in 1992 using the Argos satellite tracking techn~que (Jouventin et al 1994); during the austral summer, king penguins were found to forage mainly in a southward direction, reaching the latitude at which the Polar Front was generally located.…”
Section: Introductionmentioning
confidence: 99%